(untitled) (Research Journal, 2025)
This study examines the distribution of landslides, slope characteristics, and changes in land uses and land cover (LULC) in Ilam Municipality, Wards 8 and 9, Nepal, between 1997 and 2024. Ilam is extremely vulnerable to landslides due to its steep slopes, delicate geology, and heavy monsoon rains, which endanger livelihoods, infrastructure, and agriculture. The study tracks LULC changes and examines landslide patterns related to topographic features using Google Earth images and GIS. Positive conservation tendencies are shown by the results, which show a dramatic drop in agricultural land (64.05% to 40.20%) and an increase in forest cover (27.27% to 43.92%). However, there are urbanization issues (0% to 9.89%) in unstable areas. Topographic influence is shown by the fact that 56.70% of landslides occur on slopes between 18° and 27°, according to a slope study. Slope instability is also a result of human activity and road networks. According to the study, landslide risks are increased by uncontrolled urban growth and infrastructure development on steep terrain, even though forest expansion may assist in stabilizing slopes. To reduce the risk of landslides in the area, sustainable building methods, slope control, and efficient land-use planning are crucial.